2004
DOI: 10.1002/jnr.20179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unilateral vestibular ganglionectomy on glutaminase activity in the vestibular nerve root and vestibular nuclear complex of the rat

Abstract: The metabolism of glutamate, the most likely neurotransmitter of vestibular ganglion cells, includes synthesis from glutamine by the enzyme glutaminase. We used microdissection combined with a fluorometric assay to measure glutaminase activity in the vestibular nerve root and nuclei of rats with unilateral vestibular ganglionectomy. Glutaminase activity in the lesioned-side vestibular nerve root decreased by 62% at 4 days after ganglionectomy and remained at similar values through 30 days. No change occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…This may not be associated with changes in glutamate receptors, since Him et al (2010) reported that the responses of medial vestibular nucleus neurons to NMDA and AMPA were similar in brainstem slices from young and aged rats. It must be stressed, however, that the HPLC measurements of GABA and glutamate in the present study reflect the total pools of these amino acids in the dissected brain tissue, and only part of their total concentrations may relate to their role as neurotransmitters, while other parts relate to energy metabolism (Li et al, 1994;Li et al, 1996;Godfrey et al, 2004;Sun et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…This may not be associated with changes in glutamate receptors, since Him et al (2010) reported that the responses of medial vestibular nucleus neurons to NMDA and AMPA were similar in brainstem slices from young and aged rats. It must be stressed, however, that the HPLC measurements of GABA and glutamate in the present study reflect the total pools of these amino acids in the dissected brain tissue, and only part of their total concentrations may relate to their role as neurotransmitters, while other parts relate to energy metabolism (Li et al, 1994;Li et al, 1996;Godfrey et al, 2004;Sun et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…A possible technical explanation for some increase in receptor binding in VCN and DCNd might be a decrease in quenching after loss of lipid during degeneration of myelinated auditory nerve fibers, insofar as quenching of tritium autoradiography relates mainly to the lipid content in a region (Kuhar and Unnerstall, 1985;Kuhar, 1986;Hudson, 1993). However, loss of lipid from degenerating fiber tracts occurs very slowly in the central nervous system (McCaman and Robins, 1959); after 1 month, the loss was only 12% in the degenerating vestibular nerve root (Godfrey et al, 2004).…”
Section: Effects Of Cochlear Ablation On Muscarinic Acetylcholine Recmentioning
confidence: 99%
“…All of the procedures used in this study have been described previously (Lowry and Passonneau, 1972; Godfrey and Matschinsky, 1976; Godfrey et al, 1988, 2000, 2004b, 2008a,b; Ross et al, 1995; Li et al, 1996; Jin et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…The eluate was passed through a Spectrovision fluorescence detector, and the peaks of fluorescence were quantitated via a computer using Millennium software (from Waters). Amino acids were identified by their retention times, and their levels were calculated by comparison to calibrated amino acid standard solutions included in the same assays (Hill et al, 1979; Ross et al, 1995; Godfrey et al, 2000, 2004b, 2008a). Standards were prepared from Standard H (from Pierce) supplemented with calibrated amounts of asparagine, glutamine, taurine, and GABA (from Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation